2014
DOI: 10.1371/journal.pone.0114208
|View full text |Cite
|
Sign up to set email alerts
|

Restriction Endonucleases from Invasive Neisseria gonorrhoeae Cause Double-Strand Breaks and Distort Mitosis in Epithelial Cells during Infection

Abstract: The host epithelium is both a barrier against, and the target for microbial infections. Maintaining regulated cell growth ensures an intact protective layer towards microbial-induced cellular damage. Neisseria gonorrhoeae infections disrupt host cell cycle regulation machinery and the infection causes DNA double strand breaks that delay progression through the G2/M phase. We show that intracellular gonococci upregulate and release restriction endonucleases that enter the nucleus and damage human chromosomal DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Those genes code for restriction endonucleases. Weyler et al found restriction endonucleases, which were released by intracellular Neisseria gonorrhoeae , damaged human chromosomal DNA, and distorted mitosis [103]. Besides, some other pathogenic-associated clusters were also found in Figure 7 network, such as the nitric oxide metabolic pathway (orf_1612-orf_1620) [104] and Tfp pilus assembly protein (orf_65, orf_129, orf_1665, orf_2249, orf_528, orf_1467, and orf_1757) [105].…”
Section: Resultsmentioning
confidence: 99%
“…Those genes code for restriction endonucleases. Weyler et al found restriction endonucleases, which were released by intracellular Neisseria gonorrhoeae , damaged human chromosomal DNA, and distorted mitosis [103]. Besides, some other pathogenic-associated clusters were also found in Figure 7 network, such as the nitric oxide metabolic pathway (orf_1612-orf_1620) [104] and Tfp pilus assembly protein (orf_65, orf_129, orf_1665, orf_2249, orf_528, orf_1467, and orf_1757) [105].…”
Section: Resultsmentioning
confidence: 99%
“…Upon infection, some intestinal bacteria produce toxins that cause DNA lesions [ 170 ], potentially resulting in genome instability, and tumor initiation and progression. At the moment, four genotoxins are known to have this effect, namely colibactin (expressed by Escherichia coli ) [ 171 ], cytolethal distending toxin (CDT; expressed by certain Gram-negative bacteria [ 172 ], Shiga toxin (expressed by Shigella dysenteriae ) [ 173 , 174 , 175 ], and endonucleases (expressed by Neisseria gonorrhoeae ) [ 176 , 177 , 178 ].…”
Section: Bacteria–host Interaction and Effects On Host’s Dna Repaimentioning
confidence: 99%
“…Overall, this review highlights the immense host manipulation capabilities the gonococcus possesses to promote pathogenesis, with additional mechanisms not covered in this review surrounding the direct manipulation of the host cell growth cycle (Jones et al, 2007;Vielfort et al, 2013;Weyler et al, 2014). Nevertheless, progress toward elucidating these infection strategies in situ will greatly support advancements in both prevention and treatment of this long-lasting human disease.…”
Section: Discussionmentioning
confidence: 99%